Barriers to cardiac rehabilitation-physical activities practices: An observational descriptive study - Fatma Refaat Ahmed; Rawia Gamil Abdelhamid; Azza Hamdi El-Soussi; Mohannad Eid AbuRuz; Muhammad Arsyed Subu; Jacqueline Maria Dias; Mohamed Ibrahim Sanhoury (Elsevier, 2022)
Background: Acute phase cardiac rehabilitation has become integral to acute coronary syndrome hospitalization standard of care. However, its implementation may face barriers, and acute-phase cardiac rehabilitation practices among nurses in Egypt have yet to be evaluated. Aim and objective: To explore coronary care nurses' acute-phase cardiac rehabilitation awareness and perceived barriers to cardiac rehabilitation practices among patients with acute coronary syndrome. Design: This study used a descriptive observational research design. Methods: Convenience sampling was used, with the final sample including 25 nurses and 100 patients. Three self-administered tools were used to collect data: 1) a background questionnaire, including sociodemographic information; 2) activities of daily living questionnaire and an observational checklist to measure tolerance to physical activity; 3) an 18-item questionnaire to identify barriers to the practice of acute-phase cardiac rehabilitation. Descriptive statistics were used to analyze data. Results: Only 54% of the patients performed activities of daily living independently. Nurses had low awareness of the benefits of cardiac rehabilitation, its core components, phases, guidelines, and recommendations. Organization-related barriers ranked highest among the barriers to practice experienced by nurses (93.67 ± 13.45), followed by patient- (64.0 ± 24.73), and healthcare professional-related barriers (63.67 ± 27.83). Conclusion: Barriers related to patients, healthcare professionals, and organizations were identified as the greatest hinders to acute-phase cardiac rehabilitation practices among nurses in Egypt. Frequent assessment of these barriers in different healthcare contexts is needed.